Addition to the taxonomic and distribution records of Abernessia Arlé (Hymenoptera: Pompilidae) - Oliveira, Nathália S.; Decker, Brenna L.; Pitts, James P.; Waichert, Cecilia (Zootaxa, 2020)
Species of spider wasps (Hymenoptera: Pompilidae) are diverse in the tropical regions. The Neotropical genus Abernessia Arlé, 1947 was described from São Paulo and later found in Espírito Santo, Bahia and Minas Gerais, Brazil. Herein, we establish a neotype for the type-species A. irmgardae Arlé, discuss the previous distribution records of Abernessia in South America, add new records for Brazil, and expand the recorded distribution to San Pedro, Paraguay. The male of Abernessia giga is described and illustrated. Finally, an updated key to species known from males is provided.